Anti-inflammatory Effect of cream and ointment from 2,5- bis- (4-Nitrobenzilidine) cyclopentanoneagainst Edema in Mice Induced by Formalin - Paulina Maya Octasari; Fransiska Ayuningtyas (Universitas Sebelas Maret, 2016)
Creams and ointments are topical dosage forms used in the manufacture of drugs. Topical anti-inflammatory drug is a solution to problems of gastrointestinal side effects caused by taking nonsteroidal anti-inflammatory drug orally. The compound 2,5-bis (4-nitrobenzilidine) cyclopentanone is an analog of curcumin which has better anti-inflammatory activity than curcumin. This study aimed to determine the antiinflammatory effect of cream and ointment from 2,5-bis (4-nitrobenzilidine) cyclopentanoneagainst edema in mice induced by formalin. This research were experimental randomized complete design using a single factor. Twenty mice were divided into 4 groups: group I were given a cream base, the group II were given ointment base, group III were given cream compound 0.25% and group IV were given ointment compound 0.25%. The data were processed into AUC values and the percentage of anti-inflammatory effectwere calculated. Results were analyzed using ANOVA and T-test statistics. The results showed that between the dosage form had statistically difference of anti-inflammatory effect (p<0.05). The ointmentshowed a greater value of antiinflammatory activity rather than cream.